Characterization of Nanoscaled TiO2 Produced by Simplified Sol–Gel Method Using Organometallic Precursor - Paunović, Perica; Grozdanov, Anita; Češnovar, Andrej; Makreski, Petre; Gentile, Gennaro; Ranguelov, Bogdan; Fidančevska, Emilija (ASME International, 2015)
This work is concerned with development of sol–gel method for preparation of nanoscaled TiO2 using organometallic precursor—titanium tetraisopropoxide (TTIP) and determination of the present crystalline phases depending on the temperature of further thermal treatment. The characteristic processes and transformations during the thermal treatment were determined by means of thermal gravimetric analysis and/or differential thermal analysis (TGA/DTA) method. The crystalline structure and size of the TiO2 crystallites were analyzed by means of Raman spectroscopy and X-ray powder diffraction (XRPD) method. At 250 °C, cryptocrystalline structure was detected, where amorphous TiO2 is accompanied with crystalline anatase. The anatase crystallite phase is stable up to 650 °C, whereas at higher temperature rutile transformation begins. It was observed that at 800 °C, almost the whole TiO2 is transformed to rutile phase. According to XRPD analysis, the increase of the temperature influences on the increase of the size of the crystalline particles ranging from 6 nm at 250 °C to less than 100 nm at 800 °C. The size and shape of the TiO2 crystalline particles were observed by transmission electron microscopy (TEM). The shape of the studied samples changes from nanospheres (250, 380, and 550 °C) to nanorods (650 and 800 °C). Morphology of the formed TiO2 aggregates was observed by scanning electron microscopy (SEM).